Long-Term Zinc Fertilization in Calcareous Soils Improves Wheat (Triticum aestivum L.) Productivity and Soil Zinc Status in the Rice–Wheat Cropping System - Pepakayala Vara Lakshmi; Santosh Kumar Singh; Biswajit Pramanick; Mukesh Kumar; Ranjan Laik; Aradhna Kumari; Arvind K. Shukla; Arafat Abdel Hamed Abdel Latef; Omar M. Ali; Akbar Hossain (Agronomy, 2021)
Rice–wheat cropping system (RWCS) is considered as the furthermost vital system in the Indo-Gangetic Plains of South-Asia, including India, Pakistan, Bangladesh, and Nepal. Recently, the deficiency of micronutrients like zinc (Zn) has emerged as one of the prime limitations for the sustainability issues of this RWCS in Zn deficient calcareous soils, particularly in India, as a result of the calcareous typic ustifluvents taxonomic nature of the soils. Therefore, a new Zn fertilization approach for soils is very much needed in the intensive RWCS. Thus, a six-year-long investigation was designed with three different modes of Zn application, viz., the application of Zn only in the first year of study, application in alternative years, and application in every year. Four different rates of Zn applications in a hectare of area for a single year, viz., 2.5, 5.0, 7.5, and 10 kg ha−1 year−1, and times of Zn application, viz., only at first year, alternative years, and in each year. The major aims of the study were to determine Zn concentration in soil; yield; and Zn accumulation by wheat crop under different application methods of Zn. From this study, it was found that a large portion of the applied Zn was present in the residual fraction, and it was also revealed that increasing the frequency of Zn application resulted in the increment in the crystalline fraction. Significant correlation of water-soluble and exchangeable Zn (WS+EX-Zn), complexed Zn (COM-Zn), amorphous Zn (AMO-Zn), organic Zn (ORG-Zn), total Zn (TOT-Zn), grain yield, and grain Zn uptake by wheat indicated that these Zn fractions were dominant forms in the soil to be utilized by plants under rice–wheat rotation. Concerning yield and Zn uptake by wheat, it was noted that the Zn application at 10 kg ha−1 in alternate years was the best Zn application method, while application of Zn at 7.5 kg ha−1 in each year also resulted in comparable yield.